The Angel of Santo Tomas the story of Fe Del Mundo - Yee, Tammy; Yee, Tammy (Boston Tumblehome, Inc., 2021)
An inspiring story of a young girl from the Philippines who follows her dream to become a doctor and serve her country. Fe del Mundo's sister dreamt of becoming a doctor-a big dream for a girl in the Philippines in the early 1900s. When her sister dies, young Fe vows to take her place, a promise she carries with her the rest of her life. In 1936 she becomes the first woman and first person of Asian descent to study at Harvard Medical School. When WWII begins in the Pacific, Fe faces a choice: remain in Boston, where she is safe, or return to the Philippines, where she is needed most. Fe follows her vision and returns home to care for the American and British children forced into the internment camp at Santo Tomas. Beautiful color drawings bring to life this gentle and courageous character, her family and her patients. The story of the courageous Dr. Fe del Mundo, recipient of the Elizabeth Blackwell Award for distinguished women "whose life exemplifies outstanding service to humanity," and the Ramon Magsaysay Award, Asia's equivalent of the Nobel Prize, will inspire children to pursue science and medicine in the service of humanity"--
Ages 7-9
Grades 2-3
Keywords: Del Mundo, Fe Villanueva -- 1911-2011.; University of the Philippines Manila -- Graduates; Pediatricians -- Philippines -- Biography; Pediatricians -- Juvenile literature